Giving, Receiving, and Doing Together: Interorganizational Interactions in Age-Friendly Community Initiatives. Issue 2 (4th March 2022) - Pestine-Stevens, Althea; Greenfield, Emily A.
ABSTRACT: Multi-sectoral collaboration is widely considered essential for age-friendly community change; however, there has been little empirical research to describe the ways in which organizations interact as part of age-friendly community initiatives (AFCIs). We conducted a qualitative descriptive study using data from multiple waves of semi-structured interviews with core teams of eight grant-funded AFCIs in the north-eastern U.S. We employed iterative, inductive coding to systematically describe ways in which AFCI core teams described working with other organizational entities. Findings indicated two overarching themes: (a) helping each other (giving and receiving linking, informational, and instrumental assistance), and (b) doing something together (organizing community events, planning collaborative projects, participating in meetings). We discuss the implications of this characterization for guiding research, evaluation, and policy to optimize AFCI implementation and impact across diverse settings.